Disoriental - Djavadi, Négar, 1969- (Europa Editions, 2018)
"Kimiâ Sadr fled Iran at the age of ten in the company of her mother and sisters to join her father in France. Now twenty-five and facing the future she has built for herself as well as the prospect of a new generation, Kimiâ is inundated by her own memories and the stories of her ancestors, which come to her in unstoppable, uncontainable waves. In the waiting room of a Parisian fertility clinic, generations of flamboyant Sadrs return to her, including her formidable great-grandfather Montazemolmolk, with his harem of fifty-two wives, and her parents, Darius and Sara, stalwart opponents of each regime that befalls them"--Amazon.